The Lost History Of Christianity - "Jenkins, Philip" (New York)
"Includes bibliographical references (p. [263]-297) and index. A note on names and -isms -- The end of global Christianity -- Churches of the East -- Another world -- The great tribulation -- The last Christians -- Ghosts of a faith -- How faiths die -- The mystery of survival -- Endings and beginnings. A lost history revealing that, for centuries, Christianity's center was actually in the Middle East, Asia, and Africa, with significant communities extending as far as China."
Keywords: "CHURCH HISTORY -- PRIMITIVE AND EARLY CHURCH, CA. 30 - 600;CHRISTIAN CIVILIZATION.;CIVILIZATION, ARAB -- CHRISTIAN INFLUENCES.;MIDDLE EAST -- CHURCH HISTORY.;AFRICA, NORTH -- CHURCH HISTORY.;ASIA -- CHURCH HISTORY."